ClpV3 of the H3-Type VI Secretion System (H3-T6SS) Affects Multiple Virulence Factors in Pseudomonas aeruginosa - Li, Yanqi; Chen, Lin; Zhang, Pansong; Bhagirath, Anjali Y.; Duan, Kangmin (Frontiers in Microbiology, 2020)
The type VI secretion system (T6SS) is a toxic effector delivery apparatus widely distributed in Gram-negative bacteria. The opportunistic pathogen Pseudomonas aeruginosa encodes three T6SSs, namely H1-, H2-, and H3-T6SS. Each T6SS possesses its own effectors and their roles are not yet fully understood. Here, we report that an H3-T6SS deletion mutant PAO1(ΔclpV3) significantly affected the virulence-related phenotypes including pyocyanin production, biofilm formation, proteolytic activity and motilities. Most interestingly, the expression of T3SS genes was markedly affected, indicating a link between H3-T6SS and T3SS. RNA-Sequencing was performed to globally identify the genes differentially expressed when H3-T6SS was inactivated and the results obtained correlated well with the observed phenotypes. Interestingly, the expressions of T2SS, T3SS, H2-T6SS, and H3-T6SS were all significantly decreased, while H1-T6SS was increased in the PAO1(ΔclpV3) strain. We also observed that the intracellular concentration of secondary messenger cAMP was reduced in PAO1(ΔclpV3), and the c-di-GMP level was also decreased as indicated by the decreased cdrA reporter activity Finally, by using a Galleria mellonella infection model, we show that H3-T6SS plays a key role in the pathogenicity of P. aeruginosa in vivo . Overall, our study highlights the unique connection of H3-T6SS in P. aeruginosa with T3SS, pyocyanin production, biofilm formation and in vivo pathogenicity.